1998
DOI: 10.1001/archinte.158.7.741
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Long-term, Low-Dose, Diuretic-Based, Antihypertensive Therapy on Glucose, Lipid, Uric Acid, and Potassium Levels in Older Men and Women With Isolated Systolic Hypertension<subtitle>The Systolic Hypertension in the Elderly Program</subtitle>

Abstract: Background: Previous studies often of short duration have raised concerns that antihypertensive therapy with diuretics and ␤-blockers adversely alters levels of other cardiovascular disease risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
3
15

Year Published

1998
1998
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(176 citation statements)
references
References 40 publications
5
153
3
15
Order By: Relevance
“…However, it has been reported that diuretic usage did not slow but rather accelerates renal progression in hypertensive patients despite reducing blood pressure. For example, the EWPHE [19], SHEP [20], INSIGHT [21], and ALLHAT [17] studies all reported that the usage of diuretics was statistically associated with a greater decline in renal function compared with the other treatment groups. Thus, while diuretics reduce blood pressure and blood pressureassociated events such as stroke and heart failure, they may be less effective at slowing renal disease or reducing cardiovascular events.…”
Section: Clinical Evidence For Hyperuricemia In Renal Diseasementioning
confidence: 99%
“…However, it has been reported that diuretic usage did not slow but rather accelerates renal progression in hypertensive patients despite reducing blood pressure. For example, the EWPHE [19], SHEP [20], INSIGHT [21], and ALLHAT [17] studies all reported that the usage of diuretics was statistically associated with a greater decline in renal function compared with the other treatment groups. Thus, while diuretics reduce blood pressure and blood pressureassociated events such as stroke and heart failure, they may be less effective at slowing renal disease or reducing cardiovascular events.…”
Section: Clinical Evidence For Hyperuricemia In Renal Diseasementioning
confidence: 99%
“…Even though there is an abundance of evidence supporting the beneficial effects of thiazide diuretics on cardiovascular outcomes, these agents may accelerate the onset of T2DM in patients with hypertension (particularly when used in high doses) [77,[87][88][89][90][91][92][93], although older studies often had method limitations [93]. In the Antihypertensive and Lipid-Lowering Treatment to Prevent Heart Attacks Trial (ALLHAT) [70], the odds ratio of developing of developing T2DM at 2 years was significantly lower for lisinopril and amlodipine (0.55, P < .…”
Section: Thiazide Diuretics Clinical Datamentioning
confidence: 99%
“…Так, нестероидные противовоспалительные препараты (НПВП) умень-шают терапевтический эффект тиазидов и могут быть причиной задержки натрия. Тиазиды (но не индапа-мид) могут повышать уровень липидов (общего холе-стерина или холестерина липопротеидов низкой плот-ности) на 5-7 % в первый год терапии [15]. Основные проблемы, связанные с применением тиазидов, и пути их решения представлены в табл.…”
Section: огляд / Reviewunclassified